2021
DOI: 10.3390/ph14050434
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Gastrointestinal Survival of Non-Encapsulated and Microencapsulated Salmonella Bacteriophages: Implications for Bacteriophage Therapy in Poultry

Abstract: The therapeutic use of bacteriophages is recognized as a viable method to control Salmonella. Microencapsulation of phages in oral dosage forms may protect phages from inherent challenges of the gastrointestinal tract in chickens. Therefore, the main objective of this study was to assess the survival of Salmonella BP FGS011 (non-encapsulated and microencapsulated) through the gastrointestinal tract under in vitro as well as in vivo conditions after oral administration to 1-day-old chicks. To this end, the phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…The lack of stability upon exposure to acidic conditions (e.g., in the proventriculus/gizzard) and the relatively short residence times in the intestinal tract may limit the efficacy of orally delivered BPs [ 17 ]. To overcome these obstacles, encapsulation is proposed to provide protection from gastric acidity, releasing high doses of diet-origin BP distally [ 27 , 28 ]. In this study, we confirmed that encapsulated BP effectively delivered viable BP distally, suggesting that the encapsulation or coating of BPs may further increase their stability and viability during storage and upon ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of stability upon exposure to acidic conditions (e.g., in the proventriculus/gizzard) and the relatively short residence times in the intestinal tract may limit the efficacy of orally delivered BPs [ 17 ]. To overcome these obstacles, encapsulation is proposed to provide protection from gastric acidity, releasing high doses of diet-origin BP distally [ 27 , 28 ]. In this study, we confirmed that encapsulated BP effectively delivered viable BP distally, suggesting that the encapsulation or coating of BPs may further increase their stability and viability during storage and upon ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…BP FGS011 used in this study was isolated by Sevilla-Navarro et al [ 26 ] and characterized by Lorenzo-Rebenaque et al [ 23 ]. BP FGS011 was propagated on Salmonella Senftenberg ( S. Senftenberg), obtained from poultry farms during the NSCP [ 27 ] in the Poultry Quality and Animal Nutrition Centre of the Valencia Region (CECAV).…”
Section: Methodsmentioning
confidence: 99%
“…During this study, the BP FGS011 was evaluated without encapsulation as free BP (FP) and micro-encapsulated with the polymer Eudragit ® L100 (L100) (Evonik Nutrition & Care GmbH, Darmstadt, Germany). Encapsulation was performed according to Malik [ 28 ] and Lorenzo-Rebenaque et al [ 23 ]. For this study, the anionic polymer Eudragit ® L100 was used for the BP encapsulation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations